Konflik Kewenangan antara Penyidik Polri dan Polhut dalam Rangka Penanggulangan Tindak Pidana Pencurian Kayu - Rinaldy Amrullah (Universitas Syiah Kuala, 2013)
ABSTRACT: The effort to suppress wood theft nowadays has not optimal yet as there is an overlapping role of investigators from Forestry Department Police as Civil Servant Investigators and Indonesian National Police. It has an implication for the National Police that is not able to investigate the crime. Lack of mechanism rule of arresting by the Civil Servant Police of Forestry Department in the Forestry Act has caused different perceptions and seems it has no function causing in terms of not being caught in the act the police still needs help from the Indonesian National Police to issue the arrest letter despite the fact that the police and civil servant police has the power based on the Act Number 41, 1999 regarding forestry. The Competence of Investigation Mechanism Conflict between Police and Forestry Police in Suppressing Wood Theft